ChemInform Abstract: Direct Methylation of Amines with Carbon Dioxide and Molecular Hydrogen Using Supported Gold Catalysts. Issue 9 (February 2016) - Du, Xian‐Long; Tang, Gao; Bao, Hong‐Liang; Jiang, Zheng; Zhong, Xin‐Hua; Su, Dang Sheng; Wang, Jian‐Qiang
Abstract: The reductive methylation of cyclic amines (I) and (IV) as well as secondary amines (VI) with carbon dioxide proceeds readily in the presence of gold nanoparticles supported on γ‐alumina as a heterogeneous catalyst.